Civilian Population Victimization: A Systematic Review Comparing Humanitarian and Health Outcomes in Conventional and Hybrid Warfare. (11th April 2023) - Khorram-Manesh, Amir; Burkle, Frederick M
Abstract: Objective: The main objective of this study was to summarize the Hybrid War's core characteristics and humanitarian and medical impacts. Method: A Systematic Literature Review according to PRISMA guidelines, using the following keywords, 'Hybrid War, ' 'Humanitarian Law, ' 'Human Rights, ' 'Lawfare, ' and search engines PubMed, Scopus, Web of Science, and Gothenburg University's database to collect literature from 2000 to 2022 in English was conducted. The eligibility of qualified articles was assessed, an inductive qualitative thematic analysis was applied, and the scientific evidence of each selected piece was evaluated. Results: The objectives of a Hybrid War are to achieve the tactical and strategic goals in a battle rather than to save civilian lives. It involves networks of state and non-state actors with various means of military and militia influences and strategies, creating difficulties in implementing, controlling, and evaluating the International Humanitarian Law's "A State responsibility" principle, to gain insight into an armed conflict. It targets populated civilian areas and raises ethical and moral concerns by using Lawfare. Conclusions: Hybrid War's multi-domain action should be met with multi-dimensional approaches and a doctrine of 'acceptable losses.' Its characteristics and consequences should be learned and taught. Several measures need to be implemented to counteract its impacts, and a flexible surge capacity should be designed, planned, and executed.